Chemická zátĕz populace a její hodnocení - Fiala, Z; Srb, V; Kraják, V; Vyskocil, A (Acta medica (Hradec Kralove). Supplementum, 1998)
Human health is determined by the interplay between heredity and the environment. Air, water, food and soil contain chemical, physical and biological agents some of which are known to be harmful to health. Chemical substances that pose the risk to human health and safety and to the environment are subject to governmental regulation. The regulatory decision-making process and regulatory actions are based on two distinct elements: risk assessment and risk management. Air pollution (outdoor, indoor) is a world problem afflicting densely populated urban centers and heavily industrialised areas. Industrialization and the widespread use of chemicals coupled with modern intensive agricultural practices have raised a global concern about the contamination of soil and water. Three categories of environmental chemical contaminants generally occur in food--natural and synthetic organic compounds and traces of toxic metals. Human health protection against chemical exposure can be realised in three ways. Environmental monitoring assesses exposure to a chemical agent by measuring its concentration in the environment (i.e., air, soil, food, water). Biological monitoring assesses internal exposure to a chemical agent by measuring the chemical, its metabolites or nonadverse biological response in body fluids, tissues, expired air or excreta. Health surveillance entails the periodic medical examinations of exposed humans with the purpose of protecting health and preventing disease.
Keywords: monitorování životního prostředí; Environmental Health; Environmental Monitoring; Humans; Xenobiotics; environmentální zdraví; xenobiotika; lidé